Synthesis of Spinel Ferrite MFe2O4 (M = Co, Cu, Mn, and Zn) for Persulfate Activation to Remove Aqueous Organics: Effects of M-Site Metal and Synthetic Method - Xian, Guang; Kong, Shengyan; Li, Qiangang; Zhang, Guangming; Zhou, Ningyu; Du, Hongbiao; Niu, Lijun (Frontiers in Chemistry, 2020)
Metal species and synthetic method determine the characteristics of spinel ferrite MFe2O4. Herein, a series of MFe2O4 (M = Co, Cu, Mn, Zn) were synthesized to investigate the effect of M-site metal on persulfate activation for the removal of organics from aqueous solution. Results showed that M-site metal of MFe2O4 significantly influenced the catalytic persulfate oxidation of organics. The efficiency of the removal of organics using different MFe2O4 + persulfate systems followed the order of CuFe2O4 > CoFe2O4 > MnFe2O4 > ZnFe2O4. Temperature-programmed oxidation and cyclic voltammetry analyses indicated that M-site metal affected the catalyst reducibility, reversibility of M2+/M3+ redox couple, and electron transfer, and the strengths of these capacities were consistent with the catalytic performance. Besides, it was found that surface hydroxyl group was not the main factor affecting the reactivity of MFe2O4 in persulfate solution. Moreover, synthetic methods (sol-gel, solvothermal and co-precipitation) for MFe2O4 were further compared. Characterization showed that sol-gel induced good purity, porous structure, large surface area, and favorable element chemical states for ferrite. Consequently, the as-synthesized CuFe2O4 showed better catalytic performance in the removal of organics (96.8% for acid orange 7 and 62.7% for diclofenac) along with good reusability compared with those obtained by solvothermal and co-precipitation routes. This work provides a deeper understanding of spinel ferrite MFe2O4 synthesis and persulfate activation.